2023
DOI: 10.1038/s41388-023-02685-8
|View full text |Cite
|
Sign up to set email alerts
|

VprBP/DCAF1 regulates p53 function and stability through site-specific phosphorylation

Abstract: VprBP (also known as DCAF1) is a recently identified kinase that is overexpressed in cancer cells and serves as a major determinant for epigenetic gene silencing and tumorigenesis. The role of VprBP in driving target gene inactivation has been largely attributed to its ability to mediate histone H2A phosphorylation. However, whether VprBP also phosphorylates non-histone proteins and whether these phosphorylation events drive oncogenic signaling pathways have not been explored. Here we report that serine 367 ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Kim et al 33 identi ed that the LisH motif of DCAF1 is a negative regulator of p53, and knocking down DCAF1 leads to the activation of p53 target genes. In addition, DCAF1 weakened the p53 tumor inhibition pathway and accelerated cancer development by phosphorylating the serine 367 of p53 (S367p) 34 . Our results indicated that DCAF1 enhances the progression of GC through the activation of the PI3K/AKT/mTOR pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al 33 identi ed that the LisH motif of DCAF1 is a negative regulator of p53, and knocking down DCAF1 leads to the activation of p53 target genes. In addition, DCAF1 weakened the p53 tumor inhibition pathway and accelerated cancer development by phosphorylating the serine 367 of p53 (S367p) 34 . Our results indicated that DCAF1 enhances the progression of GC through the activation of the PI3K/AKT/mTOR pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Silencing DCAF1 resulted in defective progression through S phase, inhibited cell proliferation, triggered apoptosis, and led to early embryonic lethality [ 25 ]. Additionally, several reports have revealed that DCAF1 is involved in the development of tumors and other diseases [ 22 , 26 30 ]. Most recently, DCAF1 was further developed as an attractive target for the development of targeted protein degraders [ 31 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mutual regulation of these fluxes depends on transcriptional factor p53, a master regula-tor of energy metabolism, that is known to control perturbations of neuronal activity, particularly in epileptic seizures and upon kindling [30][31][32][33][34]. In its turn, such PTM as phosphorylation strongly regulates the function and stability of p53 [35][36][37][38]. However, specific significance of the p53 phosphorylation in epilepsy is not studied as extensively as it is in cancer [35,37].…”
Section: Introductionmentioning
confidence: 99%
“…In its turn, such PTM as phosphorylation strongly regulates the function and stability of p53 [35][36][37][38]. However, specific significance of the p53 phosphorylation in epilepsy is not studied as extensively as it is in cancer [35,37].…”
Section: Introductionmentioning
confidence: 99%